Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/vnl.22000
|View full text |Cite
|
Sign up to set email alerts
|

Application of sustainable treatments to fiber surface for performance improvement of elastomeric polyurethane reinforced with basalt fiber

Abstract: In order to overcome compatibility leakage between composite phases, which is a significant challenge in multidimensional composite applications, it is crucial to optimize the chemical nature of additives. The surface of basalt fiber (BF) was chemically enriched via biobased epoxy resin sizing and functional silanization process to improve its interfacial adhesion to the ecograde elastomeric polyurethane (EPU) matrix. The surface properties of BF were examined with the help of scanning electron microscopy X‐ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 81 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…However, the mechanical properties of fiber-reinforced composites are greatly affected by the interphase between fibers and matrix, 4 which exhibited gradient properties derived from stiff fibers to relatively weak matrix. 5 In the past decades, many methods have been proposed to improve the surface activity of carbon fiber, 6 basalt fiber, 7,8 glass fiber, 9 aramid fiber, 10 and other fibers. 11 By now, it was reported that graphene oxide (GO), 12,13 Mxene, 14 as well as carbon nanotubes (CNTs) [15][16][17] have been widely applied in surface modification of fibers to improve mechanical properties of corresponding composites.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanical properties of fiber-reinforced composites are greatly affected by the interphase between fibers and matrix, 4 which exhibited gradient properties derived from stiff fibers to relatively weak matrix. 5 In the past decades, many methods have been proposed to improve the surface activity of carbon fiber, 6 basalt fiber, 7,8 glass fiber, 9 aramid fiber, 10 and other fibers. 11 By now, it was reported that graphene oxide (GO), 12,13 Mxene, 14 as well as carbon nanotubes (CNTs) [15][16][17] have been widely applied in surface modification of fibers to improve mechanical properties of corresponding composites.…”
Section: Introductionmentioning
confidence: 99%